Innovation and authenticity: Constructing tourists’ subjective well-being in festival tourism - Zhang, Shu-Ning; Deng, Fang (Frontiers in Psychology, 2022)
Although festival tourism is an excellent fertile ground for improving individual emotions, few studies have been conducted on the influencing factors and formation mechanisms of festival tourists’ subjective well-being. To address the current research gap, this paper draws on Arnold’ s theory of emotion to examine a comprehensive formation model of tourists’ subjective well-being. The findings from 581 samples indicate that event design innovation, cultural innovation and aesthetic innovation of festival tourism are positive stimulus factors of tourists’ subjective well-being. Both experience quality and perceived festival value mediate the effects of cultural innovation and aesthetic innovation on subjective well-being, yet have no mediating effect on the relationship between event design innovation and well-being. However, it can only be achieved when festival authenticity contributes to a positive moderating effect. This study provides new ideas for the collaborative advancement of innovative development and authentic inheritance in festival tourism destinations.